KLF4: a multifunctional nexus connecting tumor progression and immune regulation - Ju, Yunjie; Xiao, Wen; Mathis, Bryan James; Shi, Ying (Frontiers in Immunology, 2025)
Krüppel-like factors (KLFs) regulate various biological processes such as cell proliferation, migration, invasion, and differentiation as gene transcription factors. Signaling pathways which mediated by KLF4 and KLF4 have a sophisticated role in tumors due to multiple factors, including the types or stage of tumors. KLF4 plays a promoter role in tumorigenesis and development, or tumor suppressor as a context-dependent anti- and pro-inflammatory factor. KLF4 over-expression increases CD8+T cell differentiation and enhances the antitumor immunity. This review aims to provide information about the relationship of KLF4 in immunity with tumors and to guide the future study.